1998
DOI: 10.1016/s0895-7061(98)00086-7
|View full text |Cite
|
Sign up to set email alerts
|

Exhaustive exercise-induced tissue hypoxia does not change endothelin and big endothelin plasma levels in normal volunteers

Abstract: Chronic hypoxia has been shown to increase plasma endothelin levels. The current study was undertaken to examine the effect of exerciseinduced tissue hypoxia on plasma levels of endothelin-1 (ET-1) and its precursor big endothelin-1 (Big-ET-1). After approval by the local ethical committee an incremental dynamic exercise test was performed in 12 physically trained volunteers (aged 20 to 40 years), using an electrically braked bicycle ergometer. The protocol included a step-wise increase of the workload until a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
3
6
1
Order By: Relevance
“…The finding in the present study of decreased plasma ET-1 levels after cycling is in agreement with the data of Richter et al [9], whereas others reported no change [19][20][21][22] or even an increase in ET-1 plasma concentrations in young athletes performing 30 min of strenuous cycling [8]. These discrepancies may be due to the small numbers of subjects investigated [21] or to differences in the protocols used, e.g., intensity of exercise [8], time of blood sampling after performance [20], or assays used for ET measurements [20,21].…”
Section: Discussionsupporting
confidence: 93%
“…The finding in the present study of decreased plasma ET-1 levels after cycling is in agreement with the data of Richter et al [9], whereas others reported no change [19][20][21][22] or even an increase in ET-1 plasma concentrations in young athletes performing 30 min of strenuous cycling [8]. These discrepancies may be due to the small numbers of subjects investigated [21] or to differences in the protocols used, e.g., intensity of exercise [8], time of blood sampling after performance [20], or assays used for ET measurements [20,21].…”
Section: Discussionsupporting
confidence: 93%
“…It is now well accepted that the plasma ET-1 level is significantly elevated under hypoxic conditions (30). It has also been reported that exercise tends to elevate ET-1 in plasma and in major organs such as heart and kidney (31)(32)(33)(34), although these results are not as conclusive as the hypoxia studies (35). So far, there is no report on whether hypoxia/exercise-induced increase in ET-1 is linked to glucose metabolism.…”
Section: Discussionmentioning
confidence: 93%
“…It is possible that subject age (children vs adults) and the particular exercise parameters used in the current study and that by Fyhrquist et al (1983) [non-incremental and thus of sustained lower intensity than Lenz et al (1998) and Arvay et al (1982)] can explain the differences between studies. Thus, it is possible that higher intensity exercise may elicit an acute response of circulating ACE activity in adults.…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies conducted in a normoxic environment using asymptomatic individuals have reported a reduction in circulating ACE activity in response to a steady-state plus incremental exercise protocol in adults (Lenz et al 1998), an increase in circulating ACE activity in response to incremental exercise in children (Avray et al 1982), and no change in response to a marathon run in adults (Fyhrquist et al 1983). It is possible that subject age (children vs adults) and the particular exercise parameters used in the current study and that by Fyhrquist et al (1983) [non-incremental and thus of sustained lower intensity than Lenz et al (1998) and Arvay et al (1982)] can explain the differences between studies.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation